PALAWIK DALAM PASUNGAN KEMISKINAN: Relasi Patron Klien dalam Industri Perikanan Kepulauan Banyak, Aceh Singkil - Fairusy, Muhajir al (Department of Anthropology, 2018)
Discussion of maritime human life and fisheries, at least be an effort to reaffirm the existence of coastal society and culture. Moreover, if the people are in the geopolitical boundaries of Aceh, which is rarely touched the attention of social researchers. This study is an attempt to understand, and describe the portrait of fisherman life of the Pulau Banyak, Aceh Singkil, which is stuck in a patron-based client relationship. Interest to study coastal communities, as an effort to see the phenomenon of poverty of fisherman community of Pulau Banyak, which is termed palawik. Therefore, it is important to see thoroughly the dynamics of the life of the fishing industry that has been held by the fishermen community. This research is descriptive, with historiography approach, and phenomenology paradigm. Data collection techniques through Library Research, and in-depth interviews with informants to find the emic side. The results showed that the Pulau Banyak fisheries industry is the main livelihood of the island community. In order to seek social security, most fishermen establish patron-clientpatterned relationships with tauke. However, the patronage pattern of working relationships has trapped and locked fishermen into poverty.